2022
DOI: 10.1111/clr.14011
|View full text |Cite
|
Sign up to set email alerts
|

The reporting and methodological quality of split‐mouth trials in oral implantology: A methodological study

Abstract: Randomized controlled trials (RCTs) are the gold standard for evaluating treatment efficacy in clinical research (Concato et al., 2000).Clinicians are more likely to make clinical decisions based on RCTs' results than observational studies, as RCTs can minimise known and unknown confounders while other study designs cannot. Therefore, researchers need to ensure that RCTs are conducted well and reported transparently.It is well-documented that the reporting and methodology of RCTs in oral implantology were poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…However, it was found that due to the mechanical connection of the two implants of different intervention Groups by superstructures, loads on one implant would be transferred to the other; which may result in carry-across effects. Carry-across effects on results cannot be tested or assessed [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, it was found that due to the mechanical connection of the two implants of different intervention Groups by superstructures, loads on one implant would be transferred to the other; which may result in carry-across effects. Carry-across effects on results cannot be tested or assessed [26].…”
Section: Discussionmentioning
confidence: 99%
“…In a split-mouth study design, quadrants within the oral cavity or each jaw are randomly allocated to receive either the treatment intervention or comparator within the same individual. [4][5][6] Advantages of this design include a reduction in the observed interindividual treatment effect variability and a reduced sample size. 4,7 Conversely, a disadvantage is the potential for carry-across effects which can bias the treatment estimates.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, several periodontal assessments taken within the same quadrant of an individual can be considered as a cluster as they represent a collection of measurements belonging to the same subject. In a split‐mouth study design, quadrants within the oral cavity or each jaw are randomly allocated to receive either the treatment intervention or comparator within the same individual 4–6 . Advantages of this design include a reduction in the observed interindividual treatment effect variability and a reduced sample size 4,7 .…”
Section: Introductionmentioning
confidence: 99%